Utility of GATA‐3 in the work‐Up of breast adenocarcinoma and its differential diagnosis in serous effusions: A Cell‐Block Microarray Study. Issue 9 (24th June 2016) - El Hag, Mohamed I.; Ha, Jennifer; Farag, Rosemary; El Hag, Amani M.; Michael, Claire W.
Abstract : Background: GATA‐3 is a transcription factor involved in human tissue growth and differentiation. It is a potential marker for breast carcinoma origin in metastasis and predictive of good prognosis. We aim to evaluate the role of GATA3 in determining the breast origin of metastatic adenocarcinoma in malignant effusions using immunohistochemistry on cell‐block microarray in comparison with ER and PR results. Methods: Cell blocks from 100 cases of malignant and reactive serous effusions with confirmed diagnosis were selected; 28 mammary carcinomas, 64 extra‐mammary adenocarcinomas (gastrointestinal, pulmonary, gynecologic), and 8 reactive mesothelium proliferation as control. Immunohistochemistry on cell‐block microarray was used. Microarray slides were stained for GATA‐3, ER and PR. Nuclear staining of >1% was considered positive. Results: GATA3, ER and PR were positive in 25 (89%), 20 (71%) and 16 (57%) of breast carcinoma cases, respectively. All non‐breast cancer cases were negative for GATA‐3 with the exception of one Müllerian adenocarcinoma (1.6%). The calculated sensitivity, specificity and positive predictive value (PPV) of GATA3 reactivity in determining the breast origin of metastatic adenocarcinoma was 89.3% ( 95% CI: 71.7–97.7% ), 98.6% ( 95% CI: 91.6–99.9% ) and 96.2% ( 95% CI: 80.4–99.9% ), respectively. GATA3 positivity was associated with ER or PR positivity in 84% of cases. Conclusions: GATA3 is a useful marker in determining the breast origin of metastatic adenocarcinoma in malignant serous effusions. Reactivity to GATA3 may indicate good prognosis. Diagn. Cytopathol. 2016;44:731–736. © 2016 Wiley Periodicals, Inc.